Horrid Henry and the tooth fairy - Simon, Francesca; Ross, Tony (London : Orion, 1997)
Age Level: 7 and up | Grade Level: 2 to 5 Horrid Henry reads Perfect Peter's diary and improves it; goes shopping with Mom and tries to make her buy him some really nice new sneakers; is horrified when his old enemy Bossy Bill turns up at school; and tries, by any means, to win the class soccer match and defeat Moody Margaret. Francesca Simon is one of the world's best-loved children's authors. She is the only American to have ever won the Galaxy Book Award, and her creation, Horrid Henry, is the #1 bestselling chapter book series in the UK--with a hit TV show and over fifteen million copies sold! Each book contains four easy-to-read
F
"A Dolphin Paperback"
b
b